Blood transfusion in Intensive Care Units: knowledge of the nursing team* (2017)
Objective: To assess the knowledge of nursing team professionals in the Intensive Care Units of blood transfusion and related factors associated with it.Methodology: Cross-sectional, quantitative study, which was carried out in three hospitals. The non-systematic sample included 104 nursing professionals working in the Intensive Care Units of these health institutions. For data collection, a checklist instrument developed and validated by the authors was used.Results: The overall knowledge score registered an average of 50.4%.The factors associated with knowledge were as follows: Training and/or guidance and monitoring of the protocols/directions to carry out the transfusion process; Frequency of blood transfusion procedures carried out by professionals; and The self-confidence factor. For etapa pré-transfusão, etapa de transfusão and etapa póst-transfusão stages, the results were 48.3%, 52.2%, and 58.3%, respectively.Conclusions: This study identified that, on the one hand, nursing professionals possess increased knowledge of post-transfusion complications; and, on the other, that self-confidence, use of protocols, training programs, and having only one job are factors associated with increased knowledge and with vigilance during the procedure.